Devices in Heart Failure Patients—Who Benefits From ICD and CRT? - Breitenstein, Alexander; Steffel, Jan (Frontiers in Cardiovascular Medicine, 2019)
Despite advances in heart failure treatment, this condition remains a relevant medical issue and is associated with a high morbidity and mortality. The cause of death in patients suffering from heart failure is not only a result of hemodynamic failure, but can also be due to ventricular arrhythmias. Implantable cardioverter defibrillators (ICDs) are these days the only tool to significantly reduce arrhythmic sudden death; but not all patients benefit to the same extend. In addition, cardiac resynchronization therapy (CRT) is another tool which is used in patients suffering from heart fialure. Even though both devices have been investigated in large randomized trials, both ICD and CRT remain underutilized in many countries. This brief review focuses on various aspects in this regard including a short overview on upcoming device novelties in the near future.